Bullseye Analysis: A Fluorescence Microscopy Technique to Detect Local Changes in Intracellular Reactive Oxygen Species (ROS) Production - Hughes, Joshua G; Chisholm, David R; Whiting, Andrew; Girkin, John M; Ambler, Carrie A (Microscopy and Microanalysis, 2023)
Reactive oxygen species (ROS) are naturally produced compounds that play important roles in cell signaling, gene regulation, and biological defense, including involvement in the oxidative burst that is central to the anti-microbial actions of macrophages. However, these highly reactive, short-lived radical species also stimulate cells to undergo programmed cell death at high concentrations, as well as causing detrimental effects such as oxidation of macromolecules at more moderate levels. Imaging ROS is highly challenging, with many researchers working on the challenge over the past 10–15 years without producing a definitive method. We report a new fluorescence microscopy-based technique, Bullseye Analysis. This methodology is based on concepts provided by the FRAP (Fluorescence Recovery after Photobleaching) technique and refined to evidence the spatiotemporal production of ROS, and the subsequent consequences, on a subcellular scale. To exemplify the technique, we have used the ROS-reporter dye, CellROX, and the ROS-inducing photosensitizer, LightOx58, a potent source of ROS compared with UV irradiation alone. Further validation of the technique was carried out using differing co-stains, notably Mitotracker and JC-1.
EPrint Processing Status: Full text deposited in DRO
Keywords: bullseye analysis; Apoptosis; Macrophages; reactive oxygen species (ROS); Reactive Oxygen Species; microscopy; photodynamic therapy (PDT); Coloring Agents; phototoxicity; Microscopy; Fluorescence; photosensitizer